Efeitos deletérios da ingestão de microplástico de polipropileno em Tilápias-do-nilo (Oreochromis niloticus) - (:unkn) unknown (Universidade Brasil, 2020)
The high molecular weight polymers, widely used in the packaging of several products, generates residues of slow degradation, accumulating in nature and transforming into microparticles during their decomposition process, being called microplastics. Based on the environmental importance represented by the accumulation of polymeric materials in aquatic organisms, the objective of this study was to evaluate the effect of daily ingestion of polypropylene microplastic on the health of tilapia (Oreochromis niloticus). Sixty fish weighing around 200 g were used, coming from the same spawning, placed in six aquariums, with a capacity of 100 L of water each (n=10). The aquariums were supplied with running water devoid of chlorine, from an artesian well, with a flow of 1 L/min, constituting the following treatments: T1: Control (without the addition of polymer), T2 and T3: (fed with ration containing 100 μg and 500 μg of polypropylene/kg of body weight, respectively). After a period of 30 days of feeding, the animals were euthanized for analysis of the blood count, leukogram, serum biochemistry, microbiological analysis of the animals' intestine, histopathological and somatic analysis of the organs. In the serum biochemical study, a significant increase in cholesterol levels and serum Aspartate Aminotransferase (AST) activity was observed in animals treated with 500 μg of polypropylene. Tilapia fed polypropylene in the diet showed an increase in thrombocyte and total leukocyte counts, marked by a significant increase in the number of circulating lymphocytes. The results of the somatic study revealed a significant increase in the stomach, liver and heart of tilapia fed with the polymer. Increase in the number of Gram-negative microorganisms and decrease in mesophilic aerobic microorganisms were observed in fish fed with the polymer. A dose-response effect was observed in these analyses. However, tilapia fed polypropylene showed deleterious effects resulting from the daily ingestion of this polymer, resulting in systemic inflammatory disorders and changes in the intestinal microbiota.
Keywords: Resíduos; Microplástico; Ecossistemas aquáticos; Aquicultura; Poluição ambiental; Organismos aquáticos; Legislação Ambiental